Artikel Review: Analisis Komparatif Bahan Tambahan pada Bioplastik Berbasis Kulit Singkong dengan Penambahan Gliserol dan Ekstrak Daun Sirih sebagai Antibakteri - Nur Handini Prisma Kustanti; Nuniek Herdyastuti (Department of Chemistry, Faculty of Mathematics and Natural Sciences, Surabaya State University, located at Jl Ketintang, Surabaya, East Java, Indonesia, 2026)
This study discusses the effect of additives on the performance of cassava peel–based bioplastics and the antibacterial effectiveness of films enriched with betel leaf extract. The analyzed parameters include water absorption, tensile strength, biodegradability, and overall film performance. The results show that glycerol produced the most flexible and balanced film, with water absorption of 15.09%, tensile strength of 1.16 MPa, and biodegradability of 60.8%. Cellulose generated mechanically strong films (7.48 MPa) but with rigid characteristics, while chitosan produced less flexible films with a tensile strength of 5.42 MPa. The addition of betel leaf extract demonstrated strong antibacterial activity, with an inhibition zone of up to 24.74 mm against Streptococcus mutans. The combination of glycerol-based bioplastic and betel leaf extract shows potential as a flexible, balanced, and active film for packaging applications.